Preparation method of high-resistivity amorphous nanocrystalline composite soft magnetic material

By introducing long silane chains into phenolic resins and coating FeCo-based amorphous nanocrystalline materials with magnesium oxide, the problem of poor performance of composite soft magnetic materials is solved, the resistivity and high temperature resistance are improved, and the magnetic loss and preparation cost are reduced. .

CN119230236APending Publication Date: 2024-12-31HUNAN JINSHAN ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411343832.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing composite soft magnetic materials have poor performance, especially due to the insufficient high temperature resistance of organic clad materials, resulting in increased magnetic loss.

Method used

The silane long chain is introduced into the phenolic resin, and the modified phenolic resin is coated with magnesium oxide with FeCo-based amorphous nanocrystalline material to improve the resistivity and performance of the composite soft magnetic material.

Benefits of technology

By coating of modified phenolic resin and magnesium oxide, the resistivity and performance of the composite soft magnetic material are significantly improved, magnetic loss is reduced, and preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230236A_ABST
    Figure CN119230236A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-resistivity amorphous nanocrystalline composite soft magnetic material in the technical field of magnetic material preparation. The composite soft magnetic material is prepared by coating a FeCo-based amorphous nanocrystalline material with modified phenolic resin and magnesium oxide. A silane long chain is introduced into the phenolic resin, the high temperature resistance of the phenolic resin is improved, and the FeCo-based amorphous nanocrystalline material is coated with the modified phenolic resin and magnesium oxide, so that the resistivity and performance of the composite soft magnetic material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic material preparation, and specifically refers to a method for preparing a high-resistivity amorphous nanocrystalline composite soft magnetic material. Background Art

[0002] Soft magnetic materials are widely used in many fields such as power electronics, information communication and energy conversion. The performance of composite soft magnetic materials is closely related to the coating material. The insulating coating material can isolate the direct contact between magnetic particles, increase the resistivity of the material, and thus reduce the magnetic loss of the material during use; insulating coating materials are generally divided into organic materials and inorganic materials. Organic coating agents have good insulation properties, simple coating methods, good integrity of the coating layer, and good formability, which can improve the mechanical strength of soft magnetic composite materials. Organic materials have poor high temperature resistance, which makes it impossible to perform high temperature heat treatment on the coating material after pressing to eliminate internal stress, resulting in increased magnetic loss.

[0003] The existing technology currently has the following main problems: the performance of composite soft magnetic materials is poor. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material. In order to solve the above problems, the present invention introduces long silane chains into the phenolic resin to improve the high temperature resistance of the phenolic resin, and coats the FeCo-based amorphous nanocrystalline material with modified phenolic resin and magnesium oxide, thereby improving the resistivity and performance of the composite soft magnetic material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material, comprising the following steps:

[0006] (1) Fe, Co, B, Si, and P are weighed and arc-melted under vacuum conditions. The melting is repeated 4-5 times to obtain an alloy ingot, which is crushed and then placed in a ball mill for 30-50 minutes. The ingot is taken out and passed through a 500-mesh sieve to obtain an alloy powder;

[0007] (2) Phenol and formaldehyde were added to a flask, and o-cresol was added. The pH value was adjusted to 8. The mixture was kept at a constant temperature of 70° C., stirred, condensed and refluxed for 1 hour, and then heated to 95° C., stirred, condensed and refluxed for 1 hour to obtain an initial product. Methylphenyldimethoxysilane was added dropwise using a dropping funnel, and the mixture was kept at a constant temperature of 95° C. for 1 hour. After the reaction was completed, the mixture was placed in a suction filtration device, and suction filtered at 70° C. and 0.1 MPa for 1 hour. The mixture was heated to 80° C. and suction filtered for 1 hour to obtain a modified phenolic resin.

[0008] (3) dissolving the modified phenolic resin described in step (2) in xylene to obtain a xylene solution, adding nano-magnesium oxide, stirring with a magnetic force for 20 min at a speed of 300 rpm, adding the alloy powder described in step (1), stirring for 1-2 h at a water bath temperature of 70° C. to obtain a composite material, placing it in a mold at a pressure of 600 MPa, maintaining the pressure for 30 s, and pressing it into a ring sample with a size of 40 mm×32 mm×8 mm;

[0009] (4) placing the annular sample described in step (3) in a crucible, placing it in a vacuum annealing furnace, heating it to 400-500° C. at a heating rate of 10° C. / min, and keeping it warm for 5-10 min to obtain a high resistivity amorphous nanocrystalline composite soft magnetic material.

[0010] Furthermore, in step (1), the Fe, Co, B, Si, and P are in the range of (Fe 0.8 Co 0.2 ) 98-x B x Si1P1 ratio, where x=13, 14 or 15.

[0011] Furthermore, in step (2), the mass ratio of phenol to formaldehyde is 1:1.3-1.4.

[0012] Furthermore, in step (2), the mass ratio of phenol to o-cresol is 300-350:1.

[0013] Furthermore, in step (2), the mass ratio of phenol to methylphenyldimethoxysilane is 6-7:1.

[0014] Furthermore, in step (3), the mass ratio of the modified phenolic resin to the alloy powder is 1:20-25.

[0015] Furthermore, in step (3), the ratio of nano magnesium oxide to alloy powder is 1:40-50.

[0016] The beneficial effects achieved by the present invention are as follows:

[0017] The invention introduces a long chain of silane into a phenolic resin to improve the high temperature resistance of the phenolic resin, and coats a FeCo-based amorphous nanocrystalline material with a modified phenolic resin and magnesium oxide, thereby improving the resistivity and performance of the composite soft magnetic material; in the amorphous nanocrystalline soft magnetic material, the B element exists in the gaps between atoms of the amorphous nanocrystalline alloy, and the amorphous forming ability of the amorphous nanocrystalline alloy strip can be improved; the Co element is used to replace part of the Fe element in the alloy, and the soft magnetic properties of the soft magnetic alloy and the plasticity of the material can be improved; the price of the P element is relatively low, and a small amount of the P element can be added in the proportioning alloy to replace the Cu element with a relatively high price, thereby reducing the preparation cost of the amorphous alloy, and the melting point of the P element is 0. The invention discloses a novel nanostructured carbon ore having a low thermal conductivity and a low molecular weight. The nanostructured carbon ore having a low thermal conductivity and a low molecular weight is prepared by introducing a silane chain into the phenolic molecule through in-situ polymerization ... BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The magnetic loss test results of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.

[0019] Figure 2 The resistivity test results of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown;

[0020] Figure 3 The coercive force test results of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.

[0021] Figure 4 This is a scanning electron microscope image of the high resistivity amorphous nanocrystalline composite soft magnetic material described in Example 1 of the present invention.

[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0025] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0026] Example 1

[0027] A method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material comprises the following steps:

[0028] (1) Fe, Co, B, Si, and P were weighed and arc-melted under vacuum conditions. Fe, Co, B, Si, and P were smelted according to (Fe 0.8 Co 0.2 ) 98-x B x Si1P1 ratio, where x=13, was smelted repeatedly for 4 times to obtain an alloy ingot, which was crushed and then put into a ball mill for grinding for 30 min, and then taken out and passed through a 500-mesh sieve to obtain an alloy powder;

[0029] (2) 10 g of phenol and 13 g of formaldehyde were added to a flask, 0.028 g of o-cresol was added, the pH value was adjusted to 8, the temperature was kept constant at 70° C., the mixture was stirred and refluxed for 1 h, and then the temperature was raised to 95° C., the mixture was stirred and refluxed for 1 h to obtain an initial product, 1.4 g of methylphenyldimethoxysilane was added dropwise using a dropping funnel, the reaction was continued at a constant temperature of 95° C. for 1 h, after the reaction was completed, the mixture was placed in a suction filtration device, suction filtered at 70° C. and 0.1 MPa for 1 h, the temperature was raised to 80° C., and suction filtered was continued for 1 h to obtain a modified phenolic resin;

[0030] (3) Dissolving 1 g of the modified phenolic resin in step (2) in xylene to obtain a xylene solution, adding 0.5 g of nano-magnesium oxide, stirring with a magnetic force for 20 min at a speed of 300 rpm, adding 25 g of the alloy powder in step (1), stirring at a water bath temperature of 70° C. for 1 h to obtain a composite material, placing it in a mold at a pressure of 600 MPa, maintaining the pressure for 30 s, and pressing it into a ring sample with a size of 40 mm×32 mm×8 mm;

[0031] (4) placing the annular sample described in step (3) in a crucible, placing it in a vacuum annealing furnace, heating it to 400° C. at a heating rate of 10° C. / min, and keeping it at that temperature for 5 min to obtain a high resistivity amorphous nanocrystalline composite soft magnetic material.

[0032] Example 2

[0033] A method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material comprises the following steps:

[0034] (1) Fe, Co, B, Si, and P were weighed and arc-melted under vacuum conditions. Fe, Co, B, Si, and P were smelted according to (Fe 0.8 Co 0.2 ) 98-x B x Si1P1 ratio, where x=15, was smelted repeatedly for 5 times to obtain an alloy ingot, which was crushed and then put into a ball mill for 50 min, and then taken out and passed through a 500-mesh sieve to obtain an alloy powder;

[0035] (2) 10 g of phenol and 14 g of formaldehyde were added to a flask, 0.03 g of o-cresol was added, the pH value was adjusted to 8, the temperature was kept constant at 70° C., the mixture was stirred and refluxed for 1 h, and then the temperature was raised to 95° C., the mixture was stirred and refluxed for 1 h to obtain an initial product, 1.7 g of methylphenyldimethoxysilane was added dropwise using a dropping funnel, the reaction was continued at a constant temperature of 95° C. for 1 h, after the reaction was completed, the mixture was placed in a suction filtration device, suction filtered at 70° C. and 0.1 MPa for 1 h, the temperature was raised to 80° C., and suction filtered was continued for 1 h to obtain a modified phenolic resin;

[0036] (3) Dissolving 1.25 g of the modified phenolic resin described in step (2) in xylene to obtain a xylene solution, adding 0.625 g of nano-magnesium oxide, stirring with a magnetic force for 20 min at a speed of 300 rpm, adding 25 g of the alloy powder described in step (1), stirring for 2 h at a water bath temperature of 70° C. to obtain a composite material, placing it in a mold at a pressure of 600 MPa, maintaining the pressure for 30 s, and pressing it into a ring sample with a size of 40 mm×32 mm×8 mm;

[0037] (4) placing the annular sample described in step (3) in a crucible, placing it in a vacuum annealing furnace, heating it to 500° C. at a heating rate of 10° C. / min, and keeping it at that temperature for 10 min to obtain a high resistivity amorphous nanocrystalline composite soft magnetic material.

[0038] Example 3

[0039] A method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material comprises the following steps:

[0040] (1) Fe, Co, B, Si, and P were weighed and arc-melted under vacuum conditions. Fe, Co, B, Si, and P were smelted according to (Fe0.8 Co 0.2 ) 98-x B x Si1P1 ratio, where x=14, was smelted repeatedly for 5 times to obtain an alloy ingot, which was crushed and then put into a ball mill for 40 minutes, and then taken out and passed through a 500-mesh sieve to obtain an alloy powder;

[0041] (2) 10 g of phenol and 13.5 g of formaldehyde were added to a flask, 0.029 g of o-cresol was added, the pH value was adjusted to 8, the temperature was kept constant at 70° C., the mixture was stirred and refluxed for 1 h, and then the temperature was raised to 95° C., the mixture was stirred and refluxed for 1 h to obtain an initial product, 1.6 g of methylphenyldimethoxysilane was added dropwise using a dropping funnel, the reaction was continued at a constant temperature of 95° C. for 1 h, after the reaction was completed, the mixture was placed in a suction filtration device, suction filtered at 70° C. and 0.1 MPa for 1 h, the temperature was raised to 80° C., and suction filtered was continued for 1 h to obtain a modified phenolic resin;

[0042] (3) Dissolving 1.2 g of the modified phenolic resin described in step (2) in xylene to obtain a xylene solution, adding 0.6 g of nano-magnesium oxide, stirring with a magnetic force for 20 min at a speed of 300 rpm, adding 25 g of the alloy powder described in step (1), stirring for 1.5 h at a water bath temperature of 70° C. to obtain a composite material, placing it in a mold at a pressure of 600 MPa, maintaining the pressure for 30 s, and pressing it into a ring sample with a size of 40 mm×32 mm×8 mm;

[0043] (4) placing the annular sample described in step (3) in a crucible, placing it in a vacuum annealing furnace, heating it to 450° C. at a heating rate of 10° C. / min, and keeping it at that temperature for 7 minutes to obtain a high resistivity amorphous nanocrystalline composite soft magnetic material.

[0044] Comparative Example 1

[0045] This comparative example provides a method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material, which differs from Example 1 in that unmodified phenolic resin is used, the preparation steps do not include step (2), and phenolic resin is used instead of modified phenolic resin in step (3), and the rest is the same as Example 1.

[0046] Comparative Example 2

[0047] This comparative example provides a method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material, which differs from Example 1 in that nano magnesium oxide is not added in step (3), and the rest is the same as Example 1.

[0048] Experimental example

[0049] 1. A broadband power analyzer was used to perform magnetic loss test on the high resistivity amorphous nanocrystalline composite soft magnetic materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 under the condition of B=50mT.

[0050] 2. The resistivity of the high-resistivity amorphous-nanocrystalline composite soft magnetic materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 was measured using a four-probe method.

[0051] 3. Under the same conditions such as external magnetic field intensity and temperature, a dynamic magnetic property measuring instrument is used to test the coercivity of the high resistivity amorphous nanocrystalline composite soft magnetic materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2.

[0052] 4. The surface morphology of the high resistivity amorphous nanocrystalline composite soft magnetic material described in Example 1 was observed using a scanning electron microscope.

[0053] Results Analysis

[0054] Figure 1 This is a graph showing the magnetic loss test results of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, Example 1 has lower magnetic loss than Comparative Examples 1 and 2.

[0055] Figure 2 This is a resistivity test result graph of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, the resistivities of Examples 1-3 are 89.1μΩ·cm, 90.2μΩ·cm, and 89.7μΩ·cm, respectively, that of Comparative Example 1 is 61.1μΩ·cm, and that of Comparative Example 2 is 57.2μΩ·cm. It can be seen that the addition of modified phenolic resin and nano-magnesium oxide greatly improves the resistivity.

[0056] Figure 3 This is a graph showing the coercive force test results of high resistivity amorphous nanocrystalline composite soft magnetic materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, the coercive forces of Examples 1-3 are 103A / m, 105A / m, and 101A / m, respectively, that of Comparative Example 1 is 124A / m, and that of Comparative Example 2 is 134A / m. It can be seen that the coercive forces of the embodiments are lower.

[0057] Figure 4 This is a scanning electron microscope image of the high resistivity amorphous nanocrystalline composite soft magnetic material described in Example 1 of the present invention.

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0059] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high resistivity amorphous nanocrystalline composite soft magnetic material, characterized in that: The specific steps include: (1) Fe, Co, B, Si, and P are weighed and arc-melted under vacuum conditions. The melting is repeated 4-5 times to obtain an alloy ingot, which is crushed and then placed in a ball mill for 30-50 minutes. The ingot is taken out and passed through a 500-mesh sieve to obtain an alloy powder; (2) Phenol and formaldehyde were added to a flask, and o-cresol was added. The pH value was adjusted to 8. The mixture was kept at a constant temperature of 70° C., stirred, condensed and refluxed for 1 hour, and then heated to 95° C., stirred, condensed and refluxed for 1 hour to obtain an initial product. Methylphenyldimethoxysilane was added dropwise using a dropping funnel, and the mixture was kept at a constant temperature of 95° C. for 1 hour. After the reaction was completed, the mixture was placed in a suction filtration device, and suction filtered at 70° C. and 0.1 MPa for 1 hour. The mixture was heated to 80° C. and suction filtered for 1 hour to obtain a modified phenolic resin. (3) dissolving the modified phenolic resin described in step (2) in xylene to obtain a xylene solution, adding nano-magnesium oxide, stirring with a magnetic force for 20 min at a speed of 300 rpm, adding the alloy powder described in step (1), stirring for 1-2 h at a water bath temperature of 70° C. to obtain a composite material, placing it in a mold at a pressure of 600 MPa, maintaining the pressure for 30 s, and pressing it into a ring sample with a size of 40 mm×32 mm×8 mm; (4) placing the annular sample described in step (3) in a crucible, placing it in a vacuum annealing furnace, heating it to 400-500° C. at a heating rate of 10° C. / min, and keeping it warm for 5-10 min to obtain a high resistivity amorphous nanocrystalline composite soft magnetic material.

2. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 1, characterized in that: In step (1), the Fe, Co, B, Si, and P are 0.8 Co 0.2 ) 98-x B x Si1P1 ratio, where x=13, 14 or 15.

3. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 2, characterized in that: In step (2), the mass ratio of phenol to formaldehyde is 1:1.3-1.

4.

4. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 3, characterized in that: In step (2), the mass ratio of phenol to o-cresol is 300-350:

1.

5. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 4, characterized in that: In step (2), the mass ratio of phenol to methylphenyldimethoxysilane is 6-7:

1.

6. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 5, characterized in that: In step (3), the mass ratio of the modified phenolic resin to the alloy powder is 1:20-25.

7. The method for preparing the high resistivity amorphous nanocrystalline composite soft magnetic material according to claim 6, characterized in that: In step (3), the ratio of nano magnesium oxide to alloy powder is 1:40-50.

Citation Information

Cited By

  • Electronic ceramic material and preparation method thereof

    CN122233762A